Phleboviruses (Family: Phenuiviridae) Worldwide, with Emphasis on the Middle East: A Systematic Review Study - Zahra Nasiri; Mohsen Kalantari; Masoumeh Amin; Salman Daliri; Kourosh Azizi (Journal of Health Sciences and Surveillance System, 2023)
Background: The prevalence of arboviruses is increasing worldwide. Their vectors are widely distributed in different continents of the world. Despite the importance of the phleboviruses, unfortunately data about the spread of the viruses in human and animal communities is very limited.Methods: This study is a systematic review of phlebovirus and its vectors worldwide, with emphasis on Middle East countries including Iran. Accordingly, all English language articles which were conducted up to the end of 2020 were found by searching the databases, including Web of Science, PubMed, Google Scholar, Science Direct, and Scopus. Furthermore, the authors used the Strobe checklist to evaluate the quality of the articles.Results: Phlebotomus perniciosus was the main vector of the Tosca virus in the Mediterranean regions such as Italy, France, and Greece. In African counties, Aedes species were more important vectors of phleboviruses, especially Rift Valley fever. As these diseases can easily spread to even uninfected areas of Asia, permanent monitoring is needed to control phleboviruses.Conclusion: Practical methods have been used to control the vectors and hosts of phleboviruses. Some important methods are listed as follows: impregnated bed nets/curtains, residual spraying, repellents, establishment of the robust surveillance of animal and their products, and limited movement of livestock during outbreak time. These methods can minimize the risk of transmission of phleboviral diseases, especially RVF infection.